COEXISTENCE OF POLYCYTHEMIA VERA AND MULTIPLE MYELOMA: A CASE REPORT - Aleksić, Sanja (Srpski medicinski časopis Lekarske komore, 2025)
Introduction: Polycythemia vera (PV) is a chronic myeloproliferative neoplasm characterized by the clonal proliferation of erythroid, myeloid, and megakaryocytic lineages, most commonly associated with the JAK2 V617F mutation. Multiple myeloma (MM), on the other hand, is a malignant plasma cell neoplasm characterized by clonal proliferation of plasma cells in the bone marrow and the secretion of monoclonal immunoglobulin. The coexistence of PV and MM in the same patient is extremely rare, as these disorders originate from distinct hematopoietic lineages. Case report: We report the case of a patient with long-standing PV who subsequently developed MM, highlighting the diagnostic and therapeutic challenges of this unusual association. Conclusion: The prognosis of patients with concomitant hematologic malignancies depends on the type and aggressiveness of the diseases, the clinical stage at the time of detection, and the adequacy of the therapeutic approach. This case highlights the importance of avoiding automatic attribution of new clinical symptoms to a pre-existing diagnosis. A broad differential diagnosis should always be maintained, with each new symptom evaluated individually, allowing for early recognition of additional hematologic pathology and timely initiation of appropriate treatment.